2013
DOI: 10.2337/dc12-2503
|View full text |Cite
|
Sign up to set email alerts
|

New-Onset Diabetes in Elderly Subjects

Abstract: OBJECTIVENew-onset diabetes mellitus (DM) in elderly patients is associated with increased risk of diabetes complications and mortality. It is unknown whether glycemic control in this population influences the mortality risk.RESEARCH DESIGN AND METHODSThe current study was conducted using the computerized database of the Sharon-Shomron District of Clalit Health Services in Israel. Included in the study were subjects 65 years of age and above with new-onset DM. The primary outcome measures were all-cause mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 15 publications
(18 reference statements)
2
19
1
Order By: Relevance
“…However, studies suggest that a higher GHbA1c level may be a serological marker to evaluate the severity and prognosis of acute brainstem infarctions (Li et al, 2012). In addition, an elevated GHbA1c level (>7.5%) was associated with an increased risk of all-cause mortality and a lower revascularization rate in elderly patients with new-onset diabetes (Twito et al, 2013). In our study, the mean GHbA1c level was 8.2% (10.5 mM).…”
Section: Discussionmentioning
confidence: 44%
“…However, studies suggest that a higher GHbA1c level may be a serological marker to evaluate the severity and prognosis of acute brainstem infarctions (Li et al, 2012). In addition, an elevated GHbA1c level (>7.5%) was associated with an increased risk of all-cause mortality and a lower revascularization rate in elderly patients with new-onset diabetes (Twito et al, 2013). In our study, the mean GHbA1c level was 8.2% (10.5 mM).…”
Section: Discussionmentioning
confidence: 44%
“…The present study found that the lowest mortality rate was among diabetic patients with HbA 1c 6.0-6.9% at baseline (new-onset diabetes), and HbA 1c 6.0-7.9% during follow-up. Two other cohort studies demonstrating the similar J-shaped association between HbA 1c and all-cause mortality also suggested that the lowest mortality rate was found among patients with HbA 1c 6.5-6.9% for new-onset diabetes [9], and with a median HbA 1c of 7.5% for long-standing diabetes (mean of diabetes duration >5 years) [8]. Based on results from the RCTs, the present study and above two epidemiological studies, the best range of HbA 1c seems to be 6.0-6.9% for new-onset diabetes and 6.0-7.9% for long-standing diabetes.…”
Section: Discussionmentioning
confidence: 87%
“…Most of the observational studies suggested a linear and positive association between HbA 1c and all-cause mortality [3-6], while others suggested that both low normal HbA 1c level and high HbA 1c level were associated with an increased risk of all-cause mortality (J or U shaped curve) [7-9]. Major reasons for the inconsistent results of the above studies might include small sample size or small number of deaths, short follow-up time, and different participant characteristics across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were trends towards higher mortality in both the HbA1c <6.5% and 7–7.4% groups, though these were not significant in the adjusted models. 5 A recent analysis of the National Health and Nutrition Examination Survey (NHANES) study from 1988–2011studied over 7,000 adults ≥65 and found that amongst those with diabetes, those with a HbA1c ≥8% had a higher risk of all-cause mortality compared to those with a HbA1c <6.5% (HR 1.6; 95% CI 1.02, 2.6). 6 The Diabetes and Aging Trial was a retrospective cohort study of 71,000 adults ≥60 with diabetes and found a U-shaped distribution in rates of mortality by HbA1c.…”
Section: Mortalitymentioning
confidence: 99%